PHYTOCHEMICAL IDENTIFICATION AND ANTIOXIDANT ACTIVITY OF JUWET FRUIT (Syzygium cumini L. Skeels) ETHANOLIC EXTRACT - Mahatya, I Made Parama Nanda; Wirawan, I Gede Putu; Suada, I Ketut (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and BiotechnologyDO - 10.24843/IJBB.2021.v08.i02.p05, 2021)
Juwet ( Syzygium cumini L. Skeels) is one of Indonesia's local fruits which its existence is hard to find now. All parts of this plant can be used for many treatments, one of which is as an antioxidant. The purpose of this study was to determine the compounds contained in the fruit and to determine the antioxidant activity as well. Phytochemical analysis was performed using the gas chromatography while antioxidant activity tests were carried out quantitatively by DPPH method. The results showed that the juwet fruit was contained phenol 284.47 mg/100 g GAE, flavonoids 379.07 mg/100g, tannins 3888.67 mg/100 g TAE and anthocyanins 40.28 mg/100 g which consisted of 66 types of chemical compounds. The results of the antioxidant analysis showed that the ethanolic extract of juwet fruit could inhibit DPPH radicals with IC 50 of 72,96 µg/ml.